A Case Study on the Use of Contexts and Socio-Scientific Issues-Based Science Education by Pre-service Junior High School Science Teachers in Indonesia During Their Final Year Teaching Internship - Nida, Safwatun; Pratiwi, Novida; Eilks, Ingo (Frontiers in Education, 2021)
This paper presents a case study looking at the use of daily life contexts and socio-scientific issues by pre-service science teachers (PSTs) in Indonesia during their final year teaching internship. The study is based on a questionnaire distributed to 42 PSTs at a State University in East-Java after they took part in a teaching internship program. The questionnaire focuses on the contexts the PSTs used in their teaching and how the contexts were used. Additionally, eight of the PSTs who taught a unit on environmental pollution were interviewed to more deeply explore how deeply they referred to real-world contexts in their teaching practice and whether or not they presented the topics as socio-scientific issues (SSIs). Most of the PSTs stated that they had used daily life contexts quite often when teaching. The most frequent contexts the PSTs used were daily life objects and questions related to society and the environment. The contexts were mostly introduced at the beginning of the lesson, before the science content was taught. They suggested that the function of contexts was generally for motivational purposes and for student engagement with science concepts. The contexts were rarely used to provoke societal discussions, even though the PSTs acknowledged that many contexts can be used in the sense of socio-scientific issues and were considered to potentially provoke discussions beyond science.